VISUALIZATION OF PEOPLEâS POSITIONS DURING THE JUNE 2021 MALUKU EARTHQUAKE IN THE VIRTUAL REALITY APPLICATION - Kautsar Fadhilah, Mochamad
On June 16, 2021, an earthquake occurred in Central Maluku. Lifesight, a company specializing in Artificial Intelligence-based location intelligence platforms for retailers, successfully collected global positioning data of the Maluku population at the time of the incident. This data holds potential for further development. This advancement is based on research concerning a framework for estimating evacuation points after disasters. This was achieved by identifying anomaly values in population density. Therefore, this research was conducted to extend the previous study into a virtual reality environment. The research outcome is a virtual reality application for visualizing the locations of people and population density during earthquakes. The creation of this application is grounded in basic data visualization theory and a framework for constructing visualizations and exploring virtual reality. The application was tested using black-box testing methods to ensure proper functionality. However, the application has not yet been able to integrate topographical information of the Maluku map. It is hoped that this application can be further developed to include such information in order to estimate evacuation points. The application successfully constructs the visualization of locations and population density during earthquakes, summarizes information from the required data for users, and explores visualization within a virtual reality environment.